PENDEKATAN PEMBELAJARAN ADAPTIF BAGI ANAK SLOW LEARNER (LAMBAN BELAJAR) DI ERA PENDIDIKAN INKLUSIF - Ika Kusumawati; Liftiah Liftiah; Ali Formen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Inclusive education provides equal opportunities for all students, including slow learners, to receive appropriate educational services according to their needs. Slow learners tend to process learning materials more slowly and therefore require adaptive learning strategies. This study aims to describe the importance of adaptive learning for slow learners in inclusive elementary schools through a literature review approach. The method used in this study was a literature review by analyzing scientific journals and books published within the last four years. The findings indicate that adaptive learning can be implemented through differentiated instruction, the use of concrete learning media, repeated instruction, individualized approaches, and collaboration between teachers and parents. These strategies improve students’ learning motivation, engagement, and conceptual understanding. Furthermore, an inclusive learning environment and teacher support are important factors in the success of adaptive learning in elementary schools.